High-Order Harmonics and Isolated-Attosecond Pulse Generation of Three-Dimensional H Atom by UV-Assisted Chirped Fields (Journal of Atomic and Molecular Sciences, 2016)
By solving the time-dependent Schrödinger equation (TDSE) accurately withtime-dependent generalized pseudospectral (TDGPS) method, we theoretically investigatedthe high-order-harmonic generation (HHG) from three dimensional (3D) Hydrogenatom in ultraviolet (UV)-assisted chirped fields. When a 128 nm UV pulse isadded on a chirped fundamental field, the HHG spectra is greatly broadened and enhanced,which is quite similar as the HHG from H atom initially prepared in the firstexcited state in the chirped field only. Besides, the HHG of H atom in the combinationof a chirped fundamental field and a 256 nm UV pulse case is also investigated.The HHG process is illustrated by the semi-classical three-step model and the time-frequencyanalysis. The ionization probability and electron wavepacket as functionsof time are also calculated to further illustrate this phenomenon. Furthermore, we alsodiscuss the influence of time delay between the chirped fundamental field and the 128nm UV pulse on HHG process. Finally, by superposing the harmonics in the range of200th-260th order, an isolated attosecond pulse with a duration of about 64 as can begenerated.